ANALYSIS OF CHANGES IN HOUSEHOLDS INCOME IN THE INTERNATIONAL RATE - Khojiev Jakhongir Dushabaevich (Innovate Conferences, 2025)
This article analyzes the dynamics of household incomes on a global scale. It examines economic, social, and demographic factors influencing the growth and decline of household incomes in various countries worldwide. Additionally, the impact of factors such as global income distribution, income inequality, the pandemic, and climate change on household well-being is explored. Based on data from international financial institutions and economic research centers, the article highlights trends in household income changes, their impact on sustainable development, and strategies for poverty reduction.